Well-being Status of Fishery Stakeholder Groups: A Comparative Study Between Improved and Poor Fish Handlers in Haor and Floodplain - Alam, A. K. M. Nowsad; Zakaria, M. U. M. Abu; Rahman, Md. Khaled; Al-Shahriar; Nuruzzaman, Mohammad (Journal of the Bangladesh Agricultural University, 2024)
This study presents a comparative analysis of well-being status between improved fish handler (IHs) and poor fish handler (PHs) groups of Kishoreganj haor and Daudkandi floodplain. Two hundred seventy respondents were surveyed randomly through structured questionnaires, focus group discussion (FGD) and key informant interview (KII) from July, 2018 to October, 2019. Young people (11-30-year group) were dominant in both the two stakeholder groups in haor and floodplain. Most of the stakeholders belonged to medium size family (5-8 persons) in both the groups. Access to education, electricity, kitchen, housing and sanitation facilities were comparatively better in IHs than PHs in both haor and Daudkandi floodplain fisheries (DFPF). In Kishoreganj haor, higher number of IHs possessed above 12 decimal of homestead land. The quality of life was comparatively better in IHs than PHs. About 45% IHs and 48.89% PHs in haor areas received health service from the Government hospitals, while it was 38.57% and 52% in DFPF, respectively. Monthly income and yearly savings were higher in IHs than PHs in both study areas. Lack of proper knowledge on pre-harvest, harvest and post-harvest handling practices of fish from fishing to transport into retail markets were found to be the major constraints of poor quality and low price of fish. IHs had comparatively better well-being status than the PHs. It is, therefore, suggested that improved fish handling must be practiced by all the stakeholder groups to improve their well-being status. J Bangladesh Agril Univ 19(1): 152–159, 2021 https://doi.org/10.5455/JBAU.5959